Genetic Characterization of Avian Influenza Viruses Isolated from the Izumi Plain, Japan in 2019/20 Winter Season - Kosuke Okuya; Ahmed Magdy Khalil; Mana Esaki; Isshu Kojima; Natsuko Nishi; Donna Koyamada; Tsutomu Matsui; Yuuhei Yoshida; Makoto Ozawa (Pathogens, 2022)
The Izumi plain in the Kagoshima Prefecture, Japan, is known as an overwintering site for more than 30,000 migratory waterfowl, including endangered crane species. We previously reported that environmental water samples, from artificial wet paddies created as crane roost sites on the Izumi plain, are useful for avian influenza virus (AIV) surveillance. During the 2019/20 winter season, we collected 238 water samples from the crane roost sites and isolated 22 AIVs of six subtypes: one H1N1, one H3N2, seven H3N8, four H4N6, nine H6N6, and one H11N2 subtypes. Genetic analyses revealed that AIVs of the same subtype isolated from the Izumi plain during a single winter season exhibited multiple genetic constellations. Furthermore, phylogenetic analyses suggested that our H3N2 isolate may be a genetic reassortant between close relatives to our H3N8 and H11N2 isolates. Our study highlighted the importance of monitoring AIV circulation to better understand AIV ecology in migratory waterfowl populations.